Effectiveness of the low FODMAP diet in patients with irritable bowel syndrome and small intestine bacterial overgrowth syndrome - Bogdanowska-Charkiewicz, Dagmara; Górski, Piotr; Jurkowska, Grażyna; Środa, Roksana; Świdnicka-Siergiejko, Agnieszka; Dąbrowski, Andrzej; Daniluk, Jarosław (Frontiers in Nutrition, 2026)
BackgroundThe low FODMAP diet (fermentable oligosaccharides, disaccharides, monosaccharides and polyols, LFD) t is used in patients diagnosed with Irritable Bowel Syndrome (IBS) as part of non-pharmacological treatment. This approach is also used in patients with Small Intestine Bacterial Overgrowth (SIBO) or Intestinal Methanogen Overgrowth (IMO), but research in this area is insufficient. To fill this gap, we decided to investigate the effect of a low FODMAP diet on various parameters in patients with IBS or SIBO or IMO. The primary end point of the study was to assess the effect of a low FODMAP diet on the severity of gastrointestinal symptoms in patients diagnosed with IBS or SIBO or IMO. Secondary end points included evaluation of patients’ tolerability of the low FODMAP diet; assessment of potential difficulties in completing a low FODMAP diet and evaluation of the role of the dietitian in the implementation of a complete low FODMAP diet.MethodsThe study was conducted using an original unvalidated questionnaire completed online by adult patients diagnosed with IBS according to Rome IV Criteria and/or SIBO/IMO patients diagnosed with hydrogen-methane breath test, treated with a low FODMAP diet.ResultsA total of 98 out of 118 patients who were invited to participate took part in an online survey. The participants had previously followed a low FODMAP diet. 90.7% of IBS patients reported reduction of symptoms after LFD. The greatest reduction in symptom severity before and after the LFD was found for bloating (MD -5.03, p < 0.001). Less than half of the patients reported diet as easy to follow and only 43,9% of patients completed LFD. 62.2% of patients were supported by a dietetitian. Patients who completed both phases of the diet were about 3.5 times more likely to improve symptoms. Those of the patients who were taking antibiotics before the diet were approximately seven times more likely to respond well to the low FODMAP diet (OR = 7.10, p = 0.028). The beneficial effect of a LFD on symptom reduction was independent of the initial diagnosis. Dividing the diet into elimination and reintroduction phases was not significantly associated with better results (p = 0.305). However, completing the entire diet program (i.e., going through both phases: elimination and reintroduction) was significantly associated with greater improvement (OR = 3.43, p = 0.024). The use of probiotics during the diet did not have a significant effect on its outcome (p = 0.529). No difference was observed between those who took them and those who did not use probiotics. Other factors (age, gender, dietary consultation, diet tolerance) – none of these factors had a significant impact on improvement after the diet – the results did not differ depending on age, gender or whether the patient had a dietary consultation.ConclusionLow FODMAP diet was well tolerated and reduced reported gastrointestinal symptoms, with the greatest effect on reducing bloating. The reduction in symptoms occurred independently of the initial diagnosis. Patients who completed both phases of the diet were taking antibiotics before the diet more likely to respond well to the low FODMAP diet. The diet proved difficult to follow, and more than half of the patients sought the support of a dietitian, which confirms the importance of such support.